Tumor characteristics and prognosis in familial breast cancer. Issue 1 (December 2016) - Arpino, G.; Pensabene, M.; Condello, C.; Ruocco, R.; Cerillo, I.; Lauria, R.; Forestieri, V.; Giuliano, M.; De Angelis, C.; Montella, M.; Crispo, A.; De Placido, S.
Abstract Background Approximately 5–10% of breast cancers are hereditary and their biology and prognosis appear to differ from those of sporadic breast cancers. In this study we compared the biological features and clinical characteristics of non metastatic breast cancer in patients with BRCA mutations versus patients with a family history suggesting hereditary breast cancer but without BRCA mutations (BRCA wild type) versus patients with sporadic disease, and correlated these findings with clinical outcome. Methods We retrieved the clinical and biological data of 33 BRCA-positive, 66 BRCA-wild type and 1826 sporadic breast cancer patients contained in a single institution clinical database between 1980 and 2012. Specifically, we recorded age, tumor size, nodal status, treatment type, pattern of relapse, second primary incidence, outcome (disease-free survival and overall survival), and biological features (estrogen receptor [ER], progesterone receptor [PgR], tumor grade, proliferation and c-erbB2 status). Median follow-up was 70 months. Results BRCA-positive patients were significantly younger than sporadic breast cancer patients, and less likely to be ER-, PgR- or c-erbB2-positive than women with BRCA-wild type or sporadic breast cancer. Tumor size and grade, nodal status and proliferation did not differ among the three groups. Rates of radical mastectomy were 58, 42 and 37%, and those of conservative surgery were 42, 58 and 63% in women with BRCA-positive, BRCA-wild type and sporadic breast cancer (p = 0.03), respectively. The incidence of contralateral breast cancer was 12, 14 and 0% (p <0.0001) and the incidence of second primary tumors (non breast) was 9, 1 and 2% (p <0.0001) in BRCA-positive, BRCA-wild type and sporadic breast cancer, respectively. Median disease-free survival in years was 29 in BRCA-wild type, 19 in BRCA-positive and 14 in sporadic breast cancer patients (log-rank = 0.007). Median overall survival in years was not reached for BRCA-wild type, 19 for BRCA-positive and 13 for sporadic breast cancer patients (log-rank <0.0001). At multivariate analyses only BRCA-wild type status was related to a significant improvement in overall survival versus the sporadic breast cancer group (HR = 0, 51; 95% CI (0, 28–0, 93)p = 0.028). Conclusions The biology and outcome of breast cancer differ between patients with BRCA mutations, patients with a family history but no BRCA mutations and patients with sporadic breast cancer.